Low-Molecular Weight Polyethylenimine Modified with Pluronic 123 and RGD- or Chimeric RGD-NLS Peptide: Characteristics and Transfection Efficacy of Their Complexes with Plasmid DNA - Jing Hu; Wenfang Zhao; Kehai Liu; Qian Yu; Yuan Mao; Zeyu Lu; Yaguang Zhang; Manman Zhu (Molecules, 2016)
To solve the problem of transfection efficiency vs. cytotoxicity and tumor-targeting ability when polyethylenimine (PEI) was used as a nonviral gene delivery vector, new degradable PEI polymers were synthesized via cross-linking low-molecular-weight PEI with Pluronic P123 and then further coupled with a targeting peptide R4 (RGD) and a bifunctional R11 (RGD-NLS), which were termed as P123-PEI-R4 and P123-PEI-R11, respectively. Agarose gel electrophoresis showed that both P123-PEI-R4 and P123-PEI-R11 efficaciously condense plasmid DNA at a polymer-to-pDNA w/w ratio of 3.0 and 0.4, respectively. The polyplexes were stable in the presence of serum and could protect plasmid DNA against DNaseI. They had uniform spherical nanoparticles with appropriate sizes around 100–280 nm and zeta-potentials about +40 mV. Furthermore, in vitro experiments showed that these polyplexes had lower cytotoxicity at any concentration compared with PEI 25 kDa, thus giving promise to high transfection efficiency as compared with another P123-PEI derivate conjugated with trifunctional peptide RGD-TAT-NLS (P123-PEI-R18). More importantly, compared with the other polymers, P123-PEI-R11 showed the highest transfection efficiency with relatively lower cytotoxicity at any concentration, indicating that the new synthetic polymer P123-PEI-R11 could be used as a safe and efficient gene deliver vector.